Pore water nutrient concentrations from sediments sampled during RV Alkor cruise AL557 - Anna Przibilla; Tina Sanders; Andreas Neumann; Carla Nantke (PANGAEA, 2023)
The samples were taken in June 2021 on the cruise AL557 in the Skagerrak and the central and southern North Sea. The samples were taken to analyze pore water concentrations of nutrients in order to monitor the nitrogen turnover processes taking place in the sediment. Pore water samples were taken with rhizon samplers (0.15 μm pore size, CSS; Rhizosphere, Netherlands) from intact sediment cores that were taken with a Multiple Corer. The samples were directly frozen until analysis on 7th and 8th March 2022. The nutrient concentrations (ammonia, silicate, phosphate, nitrite) were measured using a TECAN infinite 200 plate reader. Colorimetric methods according to Ringuet et al. (2011) for phosphate and silicate, Yu et al. (1994) for ammonia and Garcia-Robledo et al. (2014) were applied.